Quantitative Description of Duplex Stainless Steels Microstructure Using Selective Etching - Aleksandr Sergeevich Fedorov (MDPI AG, 2021)
The properties of duplex stainless steels (DSSs) depend on the ferrite–austenite ratio, on the content of secondary phases and on the contamination with non-metallic inclusions. To assess the quality of DSSs, it is necessary to use an integrated approach which includes controlling for the volume fraction, the morphology and the distribution of all phases and non-metallic inclusions. Samples of several grades of DSSs were obtained using various heat treatments, such as solution annealing and quenching from 1050 to 1250 °C to obtain different amounts of ferrite and to provoke annealing at 850 °C to precipitate σ-phase. As a result, a metallographic technique of phase analysis in DSSs based on selective etching and subsequent structure parameters estimation according to ASTM E1245 was developed. We demonstrated that the developed method of quantitative analysis based on selective etching and metallographic analysis according to ASTM E1245 allows us to obtaining much more accurate results, compared to the point count method described in ASTM E562 and to the XRD method.